Reconsidering the Switch from Low-Molecular-Weight Heparin to Unfractionated Heparin during Pregnancy - Pacheco, L. D.; Saade, G. R.; Costantine, M. M.; Vadhera, R.; Hankins, G. D. V. (American Journal of Perinatology, 2014)
Venous thromboembolic disease accounts for 9% of all maternal deaths in the United States. In patients at risk for thrombosis, common practice is to start prophylactic doses of low-molecular-weight heparin and transition to unfractionated heparin during the third trimester, with the perception that administration of neuraxial anesthesia will be safer while on unfractionated heparin, as spinal/epidural hematomas have been associated with recent use of low-molecular-weight heparin. In patients receiving prophylactic doses of unfractionated heparin, neuraxial anesthesia may be placed, provided the dose used is 5,000 units twice a day. The American Society of Regional Anesthesia and Pain Medicine guidelines recognize that the safety of neuraxial anesthesia in patients receiving more than 10,000 units per day or more than 2 doses per day is unknown, limiting the theoretical benefit of unfractionated heparin at doses higher than 5,000 units twice a day.
Keywords: low-molecular-weight heparin; neuraxial anesthesia; unfractionated heparin